Abnormal Anhedonia as a Potential Endophenotype in Obsessive–Compulsive Disorder - Xu, Chuanyong (Neuropsychiatr Dis Treat, 2020)
BACKGROUND: Obsessive–compulsive disorder (OCD) is often accompanied by cognitive, particularly executive function, impairments. Recently, anhedonia has emerged as an apparently important symptom of OCD reflecting altered emotion regulation. These two aspects are often comorbid in OCD. However, little is known about whether anhedonia may be a trait marker for OCD. METHODS: To verify the role of executive function and evaluate the role of anhedonia in OCD and its relationship with OCD symptoms, we recruited 60 OCD patients, 30 unaffected first-degree relatives (FDRs), and 60 healthy controls (HCs). Participants completed psychometric testing to assess depression, anxiety, and anhedonia symptoms, as well as two cognitive tests to assess executive function, namely the Wisconsin Card Sorting Test (WCST) and the Stroop Color-Word Test (SCWT). RESULTS: Compared to HCs, OCD patients and FDRs had significantly lower anticipatory and consummatory pleasure scores. The severity of anticipatory anhedonia correlated positively with obsessive–compulsive symptoms (r = 0.253, p = 0.009), even after controlling for depression and anxiety symptoms. Compared to HCs, OCD patients and FDRs made more errors and achieved fewer categories in the WCST. For all three SWCT components, OCD patients and FDRs took more time to name colors than HCs, but the three groups had similar numbers of errors. CONCLUSION: This family-based study showed dampened pleasure together with cognitive dysfunction in OCD patients. The similar consummatory pleasure findings between OCD and FDR groups suggest anhedonia may be considered as a candidate OCD endophenotype.